PENGARUH INTELLECTUAL CAPITAL TERHADAP KESEHATAN BANK (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Lailatul Mutmainnah; Maslichah Maslichah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2017)
ABSTRAKIntellectual Capital is generally identified as the difference between the market value of the company (enterprise business) and the assets book value of the company or its financial capital. The purpose of this study is to determine the relationship between intellectual capitals (VAICTM) formed from components of physical capital, human capital and structural capital towards bank health through RGEC (risk profile, good corporate governance, earnings, capital) approach. The data were obtained from the financial statements that have been published on the IDX by purpose sampling method. The testing between variables using partial least squares (PLS) data analysis. This study shows that there is a positive effect of intellctual capital (VAICTM) on the health of the bank. Overall, there are two indicators of intellectual capital formation (VAICTM) namely human capital (VAHU) and physical capital (VACA), but the most powerful indicator intellectual capital is VAHU. As for the bank health variables are formed from the risk profile, good corporate governance, earning, capital indicators, from these indicators, capital (CAR) is the most powerful indicator to from the bank health construction.Kata Kunci: Intellectual Capital (VAICTM), Value added Capital Employed (VACA), Value added Human Capital (VAHU), Structural Capital Coefficient (STVA), Kesehatan Bank.